Analisis Penyerapan Emisi Gas CO2 dan Serapan Karbon Jalur Hijau di Kota Surabaya, Jawa Timur - Nurabhinaya Irsyadi; Rizka Novembrianto (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Jalan Raya Kertajaya Indah and Manyar Kertoarjo are among the main road corridors in Surabaya City, heavily trafficked by various types of motorized vehicles, ranging from light to heavy-duty vehicles. The high traffic volume, especially during peak hours, causes congestion that significantly contributes to air pollution, particularly carbon dioxide (CO₂) emissions. This study aims to assess whether the CO₂ emissions produced by motor vehicles along the corridor can be absorbed by the existing roadside greenbelt vegetation. The analysis was conducted by estimating CO₂ emissions using the Intergovernmental Panel on Climate Change (IPCC, 2006) method, based on traffic counting data and specific vehicle emission factors. Furthermore, the carbon absorption capacity of the vegetation was calculated using a non-destructive sampling method by measuring tree diameter at breast height (DBH) and applying appropriate allometric equations. The results show that the total carbon dioxide emissions generated by motor vehicles traveling through Jalan Raya Kertajaya Indah and Manyar Kertoarjo in one year amount to 3,017,256.95 kg CO₂/year. Meanwhile, the total carbon absorption capacity of the greenbelt vegetation along these roads reaches 4,825,576.90 kg CO₂/year. It can thus be concluded that the carbon absorption capacity of the roadside vegetation is sufficient to offset, and even exceed, the annual CO₂ emissions generated by motor vehicle activities in this corridor.